Accommodation response to Chinese and Latin characters in Chinese‐illiterate young adults. (8th October 2015) - Radhakrishnan, Hema; Hartwig, Andreas; Charman, W Neil; Llorente, Lourdes
Abstract : Background: Differences in accommodation when reading Chinese, as compared to Latin, characters have been suggested to have a role in the higher prevalence of myopia in some Asian countries. Yeo and colleagues ( Optom Vis Sci 2013; 90: 156‐163) found that, in Chinese‐literate children, accommodation was marginally more accurate (by less than 0.05 D), when reading Chinese text. This was attributed to the additional cognitive demand associated with interpreting the more complex Chinese symbols. The present study compared responses to single Chinese and Latin characters, while controlling for cognitive demand. Methods: The monocular accommodative response was measured in Chinese‐illiterate adults (10 emmetropes, mean spherical equivalent: ‐0.07 ± 0.42 D, age: 29.9 ± 4.2 years; 11 myopes, mean spherical equivalent: ‐4.28 ± 2.84 D, age: 31.7 ± 4.6 years) with an open‐field autorefractor. Four Chinese and three Latin characters (approximately 1.15 degrees subtense) were individually presented on a display screen one metre away from the subject, while their vergence was varied over the range zero to 5.00 D using spectacle trial lenses. The slope and the accommodative error index (AEI) were calculated from the accommodative stimulus/response curves (ASRC). Results: No statistically significant differences were found between refractive groups or among characters within the same refractive group in ARSC slopes (Latin: 0.87 ± 0.14 for myopes versus 0.81 ± 0.12 for emmetropes; Chinese: 0.84 ± 0.12 for myopes versus 0.85 ± 0.12 for emmetropes). No significant differences were found between characters in accommodative error index either (Latin, 0.78 ± 0.42 D for myopes versus 1.15 ± 0.72 D for emmetropes; Chinese, 0.74 ± 0.37 D for myopes versus 1.17 ± 0.83 D for emmetropes). However, accommodative error indices and accommodative errors were significantly higher for emmetropes. Conclusion: Under controlled cognitive demand, Chinese and Latin characters elicited similar responses in both individual refractive groups. This study fails to support the hypothesis that development of myopia in some Asian populations is associated with larger lags of accommodation when reading or viewing Chinese characters.